UiTM Arau bicycle reservation app with implementation of QR Codes (Ubike college) / Muhammad Nur Hakimi Azman and Siti Zulaiha Ahmad - Azman, Muhammad Nur Hakimi; Ahmad, Siti Zulaiha (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Mobile technology supports to ease users daily activities. UiTM Arau in Perlis has launched a program called Ubike College where students and staff can use bicycle for free. Currently, they did not have any mobile applications that will make booking bicycles easier. The purpose of this study is to address the issue of making booking bicycles easier which is to develop a mobile application for the bicycle Reservation System with the implementation of QR Codes. The target users of the mobile application are students and staff in UiTM Arau. Integrated with QR Codes can ensure that users can use the bicycles at that time with only the need to scan the QR Codes.